2022
DOI: 10.1097/ico.0000000000003121
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Predicting Loss to Follow-Up, Medication Noncompliance, and Poor Visual Outcomes Among Patients With Infectious Keratitis at a Public County Hospital

Abstract: Purpose:Infectious keratitis is a vision-threatening condition requiring close follow-up and disciplined eye drop administration to achieve resolution. Although patients presenting to county hospitals often have more severe presentations, there is a paucity of risk and outcomes data in this setting. This study investigates risk factors predicting loss to follow-up (LTFU), medication noncompliance, and poor outcomes for infectious keratitis in the county hospital setting.Methods:This was a retrospective case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Our group previously reported an association of non-White race (Asian, Black, and other races) with decreased count of diagnostic and therapeutic procedures for MK (difference in the logs of expected counts,−1.3; 95% CI, −2.60 to 0.05; P = 0.05) and decreased count of visits, emails, and phone calls for MK (difference in the logs of expected counts, −0.58; 95% CI, −1.1 to −0.04; P = .03) compared with White race in a sample of 69 patients with MK. Another study found that race was not associated with final BCVA (measurement on the visit where epithelial defect was stated to be healed or if the patient was lost to follow-up, their final visit) in patients with MK. Our study also found a smaller percentage of Hispanic patients had presenting BCVA worse than 20/40 as compared with non-Hispanic patients (39.8% vs. 54.4%; P = .04).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our group previously reported an association of non-White race (Asian, Black, and other races) with decreased count of diagnostic and therapeutic procedures for MK (difference in the logs of expected counts,−1.3; 95% CI, −2.60 to 0.05; P = 0.05) and decreased count of visits, emails, and phone calls for MK (difference in the logs of expected counts, −0.58; 95% CI, −1.1 to −0.04; P = .03) compared with White race in a sample of 69 patients with MK. Another study found that race was not associated with final BCVA (measurement on the visit where epithelial defect was stated to be healed or if the patient was lost to follow-up, their final visit) in patients with MK. Our study also found a smaller percentage of Hispanic patients had presenting BCVA worse than 20/40 as compared with non-Hispanic patients (39.8% vs. 54.4%; P = .04).…”
Section: Discussionmentioning
confidence: 99%
“…18,27,[38][39][40] Specifically, patients with MK with presenting BCVA worse than 20/40 were older compared with those with better BCVA (≥20/ 40). Parmar and colleagues 39 found that a larger percentage 28 found that race was not associated with final BCVA (measurement on the visit where epithelial defect was stated to be healed or if the patient was lost to followup, their final visit) in patients with MK. Our study also found a smaller percentage of Hispanic patients had presenting BCVA worse than 20/40 as compared with non-Hispanic patients (39.8% vs. 54.4%; P = .04).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study presents positive associations between dementia, housing insecurity, and legal blindness with LOS. Housing insecurity has been previously implicated in higher rates of being lost to follow-up in patients with diabetic retinopathy and higher risk for treatment barriers such as medication noncompliance and delayed time to resolution in patients with infectious keratitis . In a previous large database study, the authors investigated the impact of housing insecurity on all hospitalizations in the US and found a trend toward longer LOS, although these results did not reach significance.…”
Section: Discussionmentioning
confidence: 99%